2013
DOI: 10.1021/ja309892e
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Sculpting in Yoctoliter Volumes

Abstract: The ability to perturb large ensembles of molecules from equilibrium led to major advances in understanding reaction mechanisms in chemistry and biology. Here, we demonstrate the ability to control, measure, and make use of rapid temperature changes of fluid volumes that are commensurate with the size of single molecules. The method is based on attaching gold nanoparticles to a single nanometer-scale pore formed by a protein ion channel. Visible laser light incident on the nanoparticles causes a rapid and larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 108 publications
6
76
0
Order By: Relevance
“…optical tweezers and microfluidic chambers 10 5−6 K/m, 46,47 fields of the order of 10 1−2 V/m could be generated at near ambient conditions while these fields could be higher, e.g. 10 2−4 V/m for the stronger thermal gradients, ∼ 10 6−8 K/m, that can be generated using metallic particles and other plasmonic structures [48][49][50] . The results presented in our work using the TIP4P/2005 model are consistent with the existence of a temperature inversion in the thermal polarization coefficient of SPC/E water.…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%
“…optical tweezers and microfluidic chambers 10 5−6 K/m, 46,47 fields of the order of 10 1−2 V/m could be generated at near ambient conditions while these fields could be higher, e.g. 10 2−4 V/m for the stronger thermal gradients, ∼ 10 6−8 K/m, that can be generated using metallic particles and other plasmonic structures [48][49][50] . The results presented in our work using the TIP4P/2005 model are consistent with the existence of a temperature inversion in the thermal polarization coefficient of SPC/E water.…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%
“…We recently tethered gold nanoparticles to the cap of the alpha-hemolysin (αHL) nanopore as a means of optically inducing a temperature change in proximity to the pore. 28 Using this concept, temperature modulation could be used to generate reaction products in a reversible fashion (e.g., temporarily melting double stranded DNA segments). Alternatively, locally enhanced temperatures could be used to momentarily increase the rate of chemical catalysis for an otherwise unfavorable reaction.…”
Section: + ⇄ a B Cmentioning
confidence: 99%
“…Metal nanoparticles and metal nanostructures can be used as nanoheaters that convert light into heat. This property is being exploited to set up nanoscale mass fluxes 7,8 and in thermal therapy applications, where the nanoparticles can bind specifically to cells. It has been shown that the temperature next to the particle can increase by hundreds of degrees, resulting in the explosive evaporation of the fluid, a phenomenon that takes place in subnanosecond timescales 9 .…”
Section: Introductionmentioning
confidence: 99%